Analisis Kualitas Data dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Badan Pusat Statistik Kota Langsa - Zuhra, Fazira; Amilia, Suri; Rahman, Maulana (DAS Institute, 2025)
This research was conducted to examine the influence of data quality and service quality on public satisfaction at PST BPS Kota Langsa, both partially and simultaneously. The data sources in this study consist of secondary data and primary data obtained through questionnaires, using a saturated sampling method with a total of 70 respondents. The analysis was carried out using multiple linear regression with the following equation: Y = 0.939 + 0.381X₁ + 0.400X₂. The t-test results indicate that both data quality (X₁) and service quality (X₂) have a significant effect on public satisfaction, with significance values of 0.004 and 0.003, respectively. The F-test also confirms a significant simultaneous effect (significance value of 0.000). The coefficient of determination (R²) of 0.570 indicates that 57% of the variation in public satisfaction can be explained by these two variables, while the remaining 43% is influenced by factors outside the scope of this study.